Reliability Quantitative Risk Assessment in Engineering System using Fuzzy Event Tree Analysis - Ouache, Rachid; Ali, A. J. Adham (INPRESSCO, 2014)
Quantitative risk assessment and reliability is most famous approach used for precise the values of possible outcomes of initiating event. The Event Tree Analysis (ETA) is a graphical logic model for assessing probability of an accident, ETA is either a preincident or a post incident application. In this paper new model proposed for reliability quantitative risk assessment using event tree analysis with a fuzzy sets approach for solve problem of uncertainty and imprecise of outcomes and risk in the chemical industry. The results got by new model is more precise and more powerful to deal with uncertainty in results and helpful for reliability quantitative risk assessment.